Compass-model physics on the hyperhoneycomb lattice in the extreme spin-orbit regime - Ryutaro Okuma; Kylie MacFarquharson; Roger D. Johnson; David Voneshen; Pascal Manuel; Radu Coldea (Nature Communications)
Abstract The physics of spin-orbit entangled magnetic moments of 4d and 5d transition metal ions on a honeycomb lattice has been much explored in the search for unconventional magnetic orders or quantum spin liquids expected for compass spin models, where different bonds in the lattice favour different orientations for the magnetic moments. Realising such physics with rare-earth ions is a promising route to achieve exotic ground states in the extreme spin-orbit limit; however, this regime has remained experimentally largely unexplored due to major challenges in materials synthesis. Here we report the successful synthesis of powders and single crystals of β-Na2PrO3, with 4f 1 Pr4+  j eff = 1/2 magnetic moments arranged on a hyperhoneycomb lattice with the same threefold coordination as the planar honeycomb. We find a strongly non-collinear magnetic order with highly dispersive gapped excitations that we argue arise from frustration between bond-dependent, anisotropic off-diagonal exchanges, a compass quantum spin model not explored experimentally so far. Our results show that rare-earth ions on threefold coordinated lattices offer a platform for the exploration of quantum compass spin models in the extreme spin-orbit regime, with qualitatively distinct physics from that of 4d and 5d Kitaev materials.